2012
DOI: 10.1111/j.1467-8640.2012.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing a Word–emotion Association Lexicon

Abstract: Even though considerable attention has been given to the polarity of words (positive and negative) and the creation of large polarity lexicons, research in emotion analysis has had to rely on limited and small emotion lexicons. In this paper we show how the combined strength and wisdom of the crowds can be used to generate a large, high-quality, word-emotion and word-polarity association lexicon quickly and inexpensively. We enumerate the challenges in emotion annotation in a crowdsourcing scenario and propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
1,001
0
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,935 publications
(1,198 citation statements)
references
References 67 publications
7
1,001
0
16
Order By: Relevance
“…Whilst GPELs offer useful knowledge about emotion-rich words, they are static and are likely to have poor coverage of the emotion vocabulary used in domains like Twitter. For emotion classification of tweets, Mohammad [17] and [22] demonstrated that DSEL based features offer significant gains over n-grams when compared to those of GPEL based features [32]. However feature extraction using DSELs has not been explored beyond binary and integer counts.…”
Section: Features For Emotion Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst GPELs offer useful knowledge about emotion-rich words, they are static and are likely to have poor coverage of the emotion vocabulary used in domains like Twitter. For emotion classification of tweets, Mohammad [17] and [22] demonstrated that DSEL based features offer significant gains over n-grams when compared to those of GPEL based features [32]. However feature extraction using DSELs has not been explored beyond binary and integer counts.…”
Section: Features For Emotion Classificationmentioning
confidence: 99%
“…Further, unfair may be associated with anger despite being more dominant in sadness related documents; the crisp binary memberships of words in GPELs do not allow to capture such fuzzy memberships of words to emotion classes, thereby making them limitedly effective for feature extraction. Accordingly, recent efforts in emotion analysis focused on learning domain specific lexicons [20,21] and also utilizing them for emotion feature extraction [17,22]. However the emotion features extracted were limited to simple emotion word counts in a document using the lexicon, which, while being simple, do not exploit the knowledge of the lexicon in its entirety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since in Mturk the annotations have been done by various workers, Cohen's j is not applicable as it needs a consistent set of annotators for all items. Therefore, like other annotation studies using crowd-sourcing (Mohammad and Turney 2012;McCreadie et al 2011;Bentivogli et al 2011), we calculated Fleiss's kappa (Fleiss 1971) for the annotation. The next section presents inter-coder agreement results.…”
Section: Inter-coder Agreement Measuresmentioning
confidence: 99%
“…The NRC Emotion Lexicon (EmoLex) is a list of English words and their associations with eight basic emotions (anger, fear, anticipation, trust, surprise, sadness, joy, and disgust) and two sentiments (negative and positive) (Mohammad & Turney 2013). The annotations were manually done by crowd sourcing.…”
Section: Affective Dictionariesmentioning
confidence: 99%